IMPLEMENTASI KEPEMIMPINAN BERBASIS FATS (FATHONAH, AMANAH, TABLIGH, SIDDIQ) TERHADAP PENINGKATAN KARAKTER PEDULI LINGKUNGAN PESERTA DIDIK SMP - Khairi, Fathul; Hartinah DS, Sitti; Apriari Fr, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of leadership based on FATS (Fathonah, Amanah, Tabligh, Siddiq) in enhancing students' environmental care character at SMP Negeri 2 Warungpring. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consisted of the school principal, teachers, and students. The findings indicate that the values of FATS leadership are implemented in school policies, environmental programs, and the exemplary behavior of the principal and teachers. The fathonah value is reflected in the visionary planning of environmental programs; amanah in the consistent execution of the programs; tabligh in conveying vision and motivation; and siddiq in exemplary and honest behavior. The implementation of FATS-based leadership has a positive impact on shaping students' environmental care character, as reflected in their active participation in cleanliness activities, waste management, and school greening efforts.